COVID-19 Vaccines: Development, Efficacy, Safety, and Global Distribution - Bilegtsaikhan Tsolmon (Pacific International Journal, 2023)
The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has had a profound impact on global public health, healthcare systems, and economies. The development and deployment of safe and effective vaccines have been a critical component of the global response to the pandemic. In this review, we provide an overview of COVID-19 vaccine development, including the various vaccine platforms used, the evaluation of vaccine efficacy and safety, and the challenges and strategies related to global vaccine distribution and administration. We also discuss the implications of emerging SARS-CoV-2 variants for vaccine effectiveness and future research directions.